The Effect Of Administrative Sanctions Enforcement On The Level Of Corporate Compliance In Waste Management In The West Java Industrial Estate - Haryono, Haryono (Fakultas Hukum Universitas Gresik, 2025)
This study aims to analyze the effect of the enforcement of administrative sanctions on the level of company compliance in waste management in the West Java Industrial Estate. The problem of industrial waste management is still an important issue, considering that many companies have not fully complied with the provisions of environmental law. Administrative sanctions, which include written reprimands, government coercion, license freezes, and license revocation, are expected to be effective instruments to improve compliance. However, its effectiveness is still often questioned in practice. This study uses a quantitative approach with a cross-sectional design. Data was collected through questionnaires and interviews with 40 companies in the Bekasi, Karawang, and Cikarang industrial estates. The analysis was performed using descriptive statistics, Pearson correlation tests, and simple linear regression with the help of SPSS software. The results showed a positive relationship between the implementation of administrative sanctions and the level of compliance, but the relationship was not statistically significant. This indicates that administrative sanctions alone are not strong enough to encourage company compliance in waste management. Other factors, such as internal company commitments, economic incentives, and public oversight, are more dominant in influencing compliance. This study concludes that a combination of legal instruments, incentives, and community participation is needed to make environmental law enforcement more effective and able to support sustainable development in Indonesia.